Advanced optimization methods for whole pelvic and local prostate external beam therapy. Issue 3 (March 2016) - Buschmann, Martin; Seppenwoolde, Yvette; Wiezorek, Tilo; Weibert, Kirsten; Georg, Dietmar
Highlights: MCO and conventional optimization were compared in prostate treatment planning. VMAT–MCO and standard VMAT optimization had similar plan quality. Hands-on planning time was reduced considerably with MCO. Whole-pelvic VMAT planning with 2 dose levels is also challenging with MCO. Abstract: Purpose: Radiation treatment planning inherently involves multiple conflicting planning goals, which makes it a suitable application for multicriteria optimization (MCO). This study investigates a MCO algorithm for VMAT planning (VMAT–MCO) for prostate cancer treatments including pelvic lymph nodes and uses standard inverse VMAT optimization (sVMAT) and Tomotherapy planning as benchmarks. Methods: For each of ten prostate cancer patients, a two stage plan was generated, consisting of a stage 1 plan delivering 22 Gy to the prostate, and a stage 2 plan delivering 50.4 Gy to the lymph nodes and 56 Gy to the prostate with a simultaneous integrated boost. The single plans were generated by three planning techniques (VMAT–MCO, sVMAT, Tomotherapy) and subsequently compared with respect to plan quality and planning time efficiency. Results: Plan quality was similar for all techniques, but sVMAT showed slightly better rectum (on average D mean −7%) and bowel sparing ( D mean −17%) compared to VMAT–MCO in the whole pelvic treatments. Tomotherapy plans exhibited higher bladder dose ( D mean +42%) in stage 1 and lower rectum dose ( D mean −6%) in stage 2 than VMAT–MCO. Compared to manual planning, the planning time with MCO was reduced up to 12 and 38 min for stage 1 and 2 plans, respectively. Conclusion: MCO can generate highly conformal prostate VMAT plans with minimal workload in the settings of prostate-only treatments and prostate plus lymph nodes irradiation. In the whole pelvic plan manual VMAT optimization led to slightly improved OAR sparing over VMAT–MCO, whereas for the primary prostate treatment plan quality was equal.